Refleksi Atas Mazmur 139:13-16 Dan Mitos Pulung Gantung Di Gunungkidul - Sariyanto, Sariyanto (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
This study discusses the phenomenon of hanging themselves in Gunungkidul, which has been going on for years and is very worrying. Similarly, cases of hanging are still common today and the numbers have remained high in the last five years. By exegesis Psalm 139:13-16, this study seeks to provide a correct understanding of human dignity and dignity. That the Bible teaches man to value life and honor God the Creator of man. The methods in this research are descriptive qualitative methods, research through exegesis, and literature studies to obtain expressions of uniqueness and wonder in the process of human creation by God. The results of the study show that psychological pressure, economic difficulties, and interpersonal conflicts are some of the common causes of hanging in Gunungkidul which has been legitimized by the myth of